Triphasic Waves and Encephalopathy in the Setting of Pregabalin Toxicity. Issue 6 (November 2018) - Anand, Pria; Kaplan, Peter Wolfe
Abstract : Summary: EEG triphasic waves are usually seen in the setting of metabolic encephalopathies, but may also occur secondary to medication toxicity. There are few reports of medications causing continuous triphasic waves, and only rare reports in the literature show an association between these discharges and pregabalin toxicity. Here, we describe triphasic waves in a patient with underlying white matter lesions, as well as pregabalin toxicity, secondary to renal insufficiency. Patients with renal or hepatic failure presenting with triphasic waves and confusion pose a diagnostic challenge in determining whether the etiology of their encephalopathy is purely metabolic or whether it results from impaired medication clearance and subsequent toxicity. In this patient, discontinuing pregabalin improved her EEG despite the ongoing renal insufficiency, confirming pregabalin toxicity as an etiology of triphasic waves and encephalopathy.